Assessment of oral health promotion services offered as part of maternal and child health services in the Tshwane Health District, Pretoria, South Africa - Yolanda Kolisa (AOSIS, 2016)
Objectives: The study aimed to assess the oral health promotion services provided as part of the maternal and child health (MCH) services in the Tshwane Health District, Pretoria, South Africa. Methods: The research design was a descriptive cross-sectional study using a modified standard questionnaire. The population was drawn from the parents/caregivers (PCGs) and the MCH nurses at seven clinics during June 2012 and June 2013 in Pretoria. Results: The nurses' response rate was 83%; average age of 37 years. The majority of the nurses (65%) were females; 60% were professional nurses. Most (63%) of the nurses reported that they provided oral health education (OHE) services. A shortage of dental education materials (43%), staff time (48%), and staff training (52%) were large constraints to nurses providing OHE. The majority of PCGs (n = 382; mean age 31.5 years) had a low education level (76%). About 55% of PCGs received information on children's oral health from the television and 35% at the MCH clinics. PCGs beliefs were worrying as about 38% believed primary dentition is not important and need not be saved. Conclusion: There is evidence of minimal integration of OHE at MCH sites. Parents' beliefs are still worrying as a significant number do not regard the primary dentition as important. The MCH site remains an important easily accessible area for integration of oral health services with general health in complementing efforts in prevention of early childhood caries. Keywords: Oral health; Promotion integration